2012
DOI: 10.1007/s10750-012-1072-6
|View full text |Cite
|
Sign up to set email alerts
|

The habitat template of phytoplankton morphology-based functional groups

Abstract: The identification of the main factors driving phytoplankton community structure is essential to understand and adequately manage freshwater ecosystems. We hypothesize that differences in morphological traits reflect phytoplankton functional properties that will be selected under particular environmental conditions, namely their habitat template. We apply a morphology-based functional groups (MBFG) approach to classify phytoplankton organisms and define each group template. We use machine learning techniques t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
84
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(100 citation statements)
references
References 62 publications
(75 reference statements)
7
84
1
8
Order By: Relevance
“…2). In contrast to the previous MBFG findings (Kruk and Segura, 2012), the MBFG R model emphasized the importance of flow velocity and suspended sediment. These results showed that the dominance of potamoplankton functional groups depends first on hydrological conditions and second on nutrients.…”
Section: Discussioncontrasting
confidence: 87%
See 4 more Smart Citations
“…2). In contrast to the previous MBFG findings (Kruk and Segura, 2012), the MBFG R model emphasized the importance of flow velocity and suspended sediment. These results showed that the dominance of potamoplankton functional groups depends first on hydrological conditions and second on nutrients.…”
Section: Discussioncontrasting
confidence: 87%
“…These species were from more than 200 lakes situated in climate zones that ranged from subpolar to tropical ones. Differences in simple morphological traits among MBFGs well reflected the significant differences in functional characteristics and habitat templates independently from the geographical location (Kruk et al, 2010;Kruk and Segura, 2012).…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations